Combating castration-resistant prostate cancer by co-targeting the epigenetic regulators EZH2 and HDAC. - Amy E Schade; Ryan Kuzmickas; Carrie L Rodriguez; Kaia Mattioli; Miriam Enos; Alycia Gardner; Karen Cichowski (PLoS Biology, 2023)
While screening and early detection have reduced mortality from prostate cancer, castration-resistant disease (CRPC) is still incurable. Here, we report that combined EZH2/HDAC inhibitors potently kill CRPCs and cause dramatic tumor regression in aggressive human and mouse CRPC models. Notably, EZH2 and HDAC both transmit transcriptional repressive signals: regulating histone H3 methylation and histone deacetylation, respectively. Accordingly, we show that suppression of both EZH2 and HDAC are required to derepress/induce a subset of EZH2 targets, by promoting the sequential demethylation and acetylation of histone H3. Moreover, we find that the induction of one of these targets, ATF3, which is a broad stress response gene, is critical for the therapeutic response. Importantly, in human tumors, low ATF3 levels are associated with decreased survival. Moreover, EZH2- and ATF3-mediated transcriptional programs inversely correlate and are most highly/lowly expressed in advanced disease. Together, these studies identify a promising therapeutic strategy for CRPC and suggest that these two major epigenetic regulators buffer prostate cancers from a lethal response to cellular stresses, thereby conferring a tractable therapeutic vulnerability.